PENGARUH MEDIA PEMBELAJARAN AR (AUGMENTED REALITY) BERBASIS 3D MENGGUNAKAN ASSEMBLR EDU TERHADAP HASIL BELAJAR SISWA KELAS IV SDN KRAMAT 1 KOTA CIREBON - Mustiranda Ginting; Nadyya Salsabila; Nugraha Permana Putra; Hendi Suhendi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN Kramat 1, Cirebon City, in the Science subject with the topic “Human Digestive System” through the use of 3D-based Augmented Reality (AR) learning media using the Assemblr Edu application. The study employed a quasi-experimental design with a pre-test, post-test, cycle 1, and cycle 2 approach, involving 25 students over 6 weeks. Data were collected through cognitive tests, observations, and interviews. The results showed a significant increase in the average student scores from 64.48 in the pre-test to 85.20 in the post-test, 89.64 in cycle 1, and 96.56 in cycle 2. Observations and interviews indicated that AR media enhanced student motivation and engagement. Based on these findings, it can be concluded that 3D-based AR learning media is effective in improving students’ cognitive learning outcomes.